PENGARUH PENGGUNAAN BATOK KELAPA DAN PASIR PANTAI TERHADAP KARAKTERISTIK CAMPURAN ASPAL - Syukuriah Katjo (Universitas Sulawesi Barat, 2023)
The construction of road pavement construction generally uses standard materials derived from natural materials such as stone and sand. However, not all regions have sufficient material reserves to be used as pavement materials or the quality of the materials is below standard. To overcome this, it is necessary to carry out technical engineering in the utilization of materials so that local materials that meet the requirements or industrial waste materials can be used optimally for road pavements, especially asphalt mixtures. As the main material in road pavement, aggregate has a very important role, where aggregate occupies the largest proportion in the mixture which generally ranges from 75% - 85% of the total volume of the mixture. One of the areas where there is a lot of coconut shell material as a substitute for coarse aggregate is Majene Regency. This study aims to find the stiffness modulus value of the AC-WC mixture using local aggregates from Majene Regency and pen oil asphalt. 60/70 as a binder due to water immersion. This research is in the form of an experiment in the laboratory. The research variables were specimens without water immersion and with water immersion for 3, 5 and 7 days. In later research using variations in asphalt content, namely 3%, 3.5%, 4%, 4.5% and 5% Keywords: Coconut shell, Asphalt Pen 60/70, immersion, stiffness, waste materials